Response of leaf stoichiometry of Potentilla anserina to elevation in China's Qilian Mountains - Zhang, Xiaofang; Feng, Qi; Cao, Jianjun; Biswas, Asim; Su, Haohai; Liu, Wei; Qin, Yanyan; Zhu, Meng (Frontiers in Plant Science, 2022)
Plants adapt to changes in elevation by regulating their leaf ecological stoichiometry. Potentilla anserine L. that growth rapidly in poor or even bare soil conditions, has become an important ground cover plant for ecological restoration. However, its leaf ecological stoichiometry has given little attention, resulting in insufficient understanding of its environmental adaptability and growth strategies. The objective of this study was to compare the leaf stoichiometry of P. anserine at different elevations (2400 m, 2600 m, 2800 m, 3000 m, 3200 m, 3500 m and 3800 m) in the middle eastern Qilian mountains. With the increase in elevation, leaf carbon concentration ([C]leaf) significantly decreased, with the maximum value of 446.04 g·kg-1 (2400 m) and the minimum value of 396.78 g·kg-1 (3500 m). Leaf nitrogen concentration ([N]leaf) also increased with increase in elevation, and its maximum and minimum values were 37.57 g·kg-1 (3500 m) and 23.71 g·kg-1 (2800 m), respectively. Leaf phosphorus concentration ([P]leaf) was the highest (2.79 g·kg-1) at 2400 m and lowest (0.91 g·kg-1) at 2800 m , respectively. The [C]leaf:[N]leaf decreased with increase in elevation, while [N]leaf:[P]leaf showed an opposite trend. The mean annual temperature, mean annual precipitation, soil pH, organic carbon, nitrogen, and phosphorus at different elevation mainly affected [C]leaf, [N]leaf, and [P]leaf. The growth of P. anserine in the study area was mainly limited by P, and this limitation was stronger with increased elevation. Progressively reducing P loss at high elevation is of great significance to the survival of P. anserine in this specific region.